تطبيق نظرية اللعبة في اختيار استراتيجية ملائمة لتوسيع شبكة كهربائية - أحمد, أحمد سليمان; حيدر, تمّام; قصير, ميساء (Latakia University Journal -Engineering Sciences Series, 2019)
يعتبر موضوع تخطيط وتوسيع الشبكات الكهربائية موضوعاً هامّاً وحسّاساً لارتباطه بالنمو الاقتصادي للبلد وتأمين مصادر الطاقة والنموّ السكاني، وغيرها من العوامل. يزداد الطلب على القدرة الكهربائية بشكل كبير، ويترافق ذلك مع تغيرات هامّة في سوق القدرة الكهربائية كتحرير السوق، ودخول موزعي القدرة المستقلين، بالإضافة إلى تنامي الاهتمام بمصادر الطاقة المتجددة وفرض معايير تتعلق بالبيئة، وغيرها. أدّت هذه التطورات مجتمعة إلى ضرورة دراسة موضوع تخطيط الشبكات الكهربائية مع اعتبار المعايير الجديدة. اختيرت نظرية اللعبة بهدف الحصول على حلّ توفيقي أمثل من بين مجموعة من الحلول المقترحة وذلك من وجهة نظر مجموعة من المعايير متعارضة الأهداف. نقوم في هذا العمل بتوصيف الصياغة الرياضية لمواقف اتخاذ القرار، وبناء خوارزمية تقوم بتحديد استراتيجية الحل التوفيقي الأمثل لهذه المواقف. تمّ بناء برنامج يعتمد على نظرية اللعبة بمساعدة البيئة البرمجية Matlab، لاختيار الحلّ التوفيقي الأمثل. اختبرت فعالية الطريقة بتطبيقها على شبكة كهربائية تحتاج إلى توسيع. Power system planning and expanding is an important and sensitive subject, because of its correlation with the economic development of the country, power resources, population growth and many other factors. In the recent decades, the demand of the electric power has increased dramatically. This is associated with the important changes in power market that are the result of many factors: the liberalization of energy market, the emergence of independent power producers, the growing interest in renewable energy resources, and the application of new criteria concerned with the environment, and other issues. All of these changes require the study of electric power-system planning putting in mind the new criteria. The game-theory is chosen to obtain an optimal compromising solution among a set of the recommended solutions; this is in the light of the criteria with opposing goals. In this work, we provide a description of the mathematical formula for the decision making positions and we aim to develop an algorithm that determines the optimal-compromising solution strategy for such positions. The Matlab environment helps to construct a software for choosing the optimal-compromising solution based on the game-theory. The effectiveness of such approach has been demonstrated by being applied to an electrical network suffering from specific problems and in need to be expanded.